Representaciones sociales de las comunidades sobre la escuela :Estudio de caso en 4 escuelas de Cayambe y Pedro Moncayo - Caluguillin Cuascota, José Julián (2015)
The social representations of communities about school. Case study in four schools of Cayambe and Pedro Moncayo theme we investigated, and this has been a great opportunity for us to know the reality of the communities, to systematize and make analyze the information collected and field unpoco of theory. There are actually a lot of research about the school and have not reached deep to find his past in school and problems spanning, without classrooms, teaching materials, teachers for each grade in that for good teaching and learning the better performance in their studies. Who collaborated on this study were male and female parents and mothers of Cayambe and Pedro Moncayo, usually have seen women are more aware of the school and their sons / daughters and men for their activities are bit away from their families but it has gained a very information of lived reality. These visits by the communities we have seen, have touched that this research has helped us understand the experience of the school of social representation of communities. Respondents have seen questions that are required as essential and serve as an experience for youth to see the true experience of parents, study without much infrastructure, lack of teaching materials and teachers themselves one teacher contributions to improve the school structure.